Humanisme menurut Niccolo Machiavelli - Daya Negri Wijaya; Mashuri Mashuri; Ulfatun Nafi’ah (Jurnal Teori dan Praksis Pembelajaran IPS, 2017)
Machiavelli as inspired by his age wants to open people’s awareness at present. He is shaped by the spirit of renaissance then his thoughts seem to be more humanistic. However people claim that his thinking is amoral but he suggests the humanistic recommendation. He advises that the prince should decide any decision to reach his aims. Unless, people tend to ignore how he advices to be a humanistic prince. In his work entitled “Discourse”, he even wants to deconstruct and direct people to be more humanistic. He believes that the nature of man is envy and is like to criticize than to appreciate so that man will repeat his conflict as long as his life. The worshipping of past steers the man to think irregularly. It is a time to know history from not only the past but also the past and the present. KeywordsRenaissance, Humanistic Prince, Historical Thinking, Humanism http://dx.doi.org/10.17977/um022v2i22017p053